Biomarkers for Successful IVF and ICSI: a Systematic Review - Pawong, Chanya; Chaijaroenkul, Wanna (Journal of Basic and Applied Pharmacology, 2025)
Assisted reproductive technologies (ART), including in vitro fertilization (IVF) and intracytoplasmic sperm injection (ICSI), have revolutionized infertility treatment. However, their success remains variable and depends on multiple biological and clinical factors. Biomarkers have emerged as promising tools for predicting, monitoring, and potentially improving ART outcomes. Despite extensive research, no biomarker has been adopted for routine clinical use. This systematic review aims to examine emerging biomarkers identified in serum, follicular fluid, follicular cells, culture medium, endometrial tissue, and cumulus granulosa cells, to provide a comprehensive understanding of their potential impact on ART outcomes. The publications were searched in PubMed and ScienceDirect from inception to May 25, 2024. Inclusion criteria were: (i) patients undergoing ICSI or IVF, (ii) biomarkers related to implantation and/or pregnancy outcomes, (iii) studies primarily focused on biomarkers, and (iv) full-text original articles. Exclusion criteria were: (i) non-English publications, (ii) review articles, (iii) unrelated outcomes, and (iv) studies involving reproductive system diseases or diagnosed reproductive disorders. A total of 47 studies met the inclusion criteria and were analyzed to synthesize current evidence on biomarkers and evaluate their potential relevance to ART outcomes. Numerous biomarkers were identified across various biological samples. Hormonal biomarkers are the most consistently reliable, with follicle-stimulating hormone to luteinizing hormone (FSH/LH) ratios and anti-Müllerian hormone (AMH) levels demonstrating utility in assessing ovarian reserve and predicting reproductive potential. In addition to hormonal indicators, molecular signatures (gene and protein expression profiles, cytokines, and other non-traditional biomarkers) have been widely investigated. However, no single biomarker or panel has yet shown sufficient predictive power, sensitivity, or specificity for routine clinical use. Nonetheless, certain biomarkers may offer therapeutic insights and inform novel intervention strategies. These findings underscore the complexity of human reproduction and highlight the need for integrated, large-scale research involving diverse populations to identify reliable biomarkers that can support evidence-based decision-making in reproductive medicine.